Determinants of Travel Participation and Experiences of Wheelchair Users Traveling to the Bodrum Region: A Qualitative Research - Özcan, Ezgi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Although there has been an increasing tendency in the number of people with disabilities and types of disability day by day, a sufficient point was not reached regarding accessible tourism. Further, the participation rate of people with disabilities (PWDS) in tourism activities tends to get low and a big gap is observed in the travel and accommodation sector in this regard. On the other side, previous studies have concluded that the accessible tourism market was a significant and profitable area. The main purpose of this study is to determine the determinants of travel by examining the motivations, expectations, processes, and experiences of PWDS using wheelchairs to participate in tourism. The obtained outcomes revealed that wheelchair users intended to go on vacation but were less motivated to participate due to insufficient travel conditions. The wheelchair travellers argued that a companion was required for an enjoyable holiday that could meet their needs. It was also revealed that the wheelchairs disabled people use were not suitable to be used on the beach, sand, or in water. Furthermore, by exploring the heterogeneous nature of wheelchair users, their motivation in tourism with the effect of internal and environmental factors, this research added a great contribution to the industry in terms of providing products and services in the tourism sector. It is also considered to provide insights for future studies.

ÖZ: Engelli sayısı ve engel türlerinde her geçen gün artan bir eğilim olmasına rağmen erişilebilir turizm konusunda yeterli noktaya gelinememiştir. Ayrıca, engellilerin (EBÖ) turizm faaliyetlerine katılım oranı düşme eğilimi göstermekte ve bu konuda seyahat ve konaklama sektöründe büyük bir boşluk gözlemlenmektedir. Öte yandan, önceki çalışmalarda erişilebilir turizm pazarının önemli ve karlı bir alan olduğu sonucuna varılmıştır. Bu çalışmanın temel amacı, turizme katılmak için tekerlekli sandalye kullanan engellilerin motivasyonlarını, beklentilerini, süreçlerini ve deneyimlerini inceleyerek seyahatin belirleyicilerini belirlemektir. Elde edilen sonuçlar, tekerlekli sandalye kullanıcılarının tatile çıkmayı düşündüklerini ancak yetersiz seyahat koşulları nedeniyle katılım konusunda daha az motive olduklarını ortaya koydu. Tekerlekli sandalye ile seyahat edenler, ihtiyaçlarını karşılayabilecek keyifli bir tatil için bir refakatçiye ihtiyaç olduğunu savundu. Engellilerin kullandığı tekerlekli sandalyelerin plajda, kumda ve suda kullanıma uygun olmadığı da ortaya çıktı. Ayrıca bu araştırma, tekerlekli sandalye kullanıcılarının heterojen yapısını, iç ve çevresel faktörlerin etkisiyle turizmdeki motivasyonlarını keşfederek, turizm sektöründe ürün ve hizmet sunumu açısından sektöre büyük katkı sağlamıştır. Ayrıca gelecekteki çalışmalara ışık tutacağı düşünülmektedir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Co-Supervisor: Asst. Prof. Dr. Zahra Güçhan Topçu and Supervisor: Prof. Dr. Hüseyin Araslı
Keywords: Thesis Tez